Facile synthesis of tough metallosupramolecular hydrogels by using phosphates as temporary ligands of ferric ions to avoid inhibition of polymerization. Issue 15 (19th January 2022) - Fang, Lingtao; Hu, Jian; Zhang, Chuan Wei; Wei, Jialun; Yu, Hai Chao; Zheng, Si Yu; Wu, Zi Liang; Zheng, Qiang
Abstract: Forming carboxyl‐Fe 3+ coordination bonds as physical crosslinks is an effective strategy to develop tough hydrogels. Considering the inhibition of ferric ions on free‐radical polymerization, these coordination bonds cannot be formed during the reaction, and a soaking process of preformed hydrogels is usually required for mechanical enhancement, resulting in uncontrollable gradient structure, long preparation time, and unnecessary waste of metallic ions. A facile strategy is reported here to prepare tough metallosupramolecular hydrogels by polymerization and in situ formation of coordination bonds with phosphates as the temporal ligands of Fe 3+ ions. The phosphate ligands in the precursor solution form coordination complexes with the Fe 3+ ions, which avoids the inhibition and ensures the polymerization. After swelling the resultant hydrogel in water, the ligands are substituted by carboxyl groups of the gel matrix due to the variation of local pH. The equilibrated hydrogel with carboxyl‐Fe 3+ coordination bonds as the physical crosslinks possesses excellent mechanical properties that can be tuned over a wide range by adjusting the polymer compositions and the concentrations of phosphate ligands and Fe 3+ ions. This strategy should be applicable to other systems to enable synthesis of functional hydrogels with Fe 3+ ions as the additive toward specific applications in engineering and biomedical fields. Abstract :